VICTIM BLAMING: LABELING FOR WOMEN VICTIMS OF SEXUAL VIOLENCE IN HUMAN RIGHTS PERSPECTIVE - Darma, I Made Wirya; Triwulandari, I Gusti A A Mas; Bunga, Dewi (International Journal of Law Reconstruction, 2022)
The problem of blaming victims is related to the strong traditions and culture of the community that still perpetuate gender stereotypes. This study aims to examine the implications of patriarchal culture on the position of women as subordinates, the concept of blaming the victim against the women victims of sexual violence and human rights studies on victim blaming and labeling for women victims of sexual violence. The culture of gender injustice in the society makes women often get negative labels, in which the women who look beautiful and dress up using rather tight and sexy clothes are always considered as inviting the opposite sex to commit sexual harassment. This is then always used and associated with labeling of victims of sexual harrasment in which the society tends to blame victims of sexual harrasment or victim blaming. This type of research is a normative juridical research that is prescriptively providing solutions to the legal protection for victims related to victim blaming and labeling women as victims of sexual violence in the view of human rights that difinitely violates the constitution and law.